PENGARUH WORD OF MOUTH DAN TRAVEL MOTIVATION TERHADAP MINAT BERKUNJUNG KE PANTAI TIKUS EMAS SUNGAILIAT KABUPATEN BANGKA: Pengaruh Word Of Mouth dan Travel Motivation Terhadap Minat Berkunjung Ke Pantai Tikus Emas Sungailiat Kabupaten Bangka - Advent Sipahutar, Onedes; Christianingrum, Christianingrum; Yanuar, Donny (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
The background of this study was the word of mouth and travel motivation can influence interest in visiting as a phenomena that occur in society The purpose of this research is to get an overview and know the effect of word of mouth and travel motivation on the interest of visiting Pantai Tikus Emas Sungailiat, Bangka Regency. Testing instruments using multiple linear regression analysis methods. The result shows that So it can be concluded that word of mouth and travel motivation has a positive and significant effect on visiting interest. The result of the coefficient of determination show that the word of mouth and travel motivation variabels affect the visiting interest by 58,9%.